Recent trends and perspectives in reconstruction and regeneration of intra/extra-oral wounds using tissue-engineered oral mucosa equivalents - Kenji Izumi; Witsanu Yortchan; Yuka Aizawa; Ryota Kobayashi; Emi Hoshikawa; Yiwei Ling; Ayako Suzuki (Japanese Dental Science Review, 2023)
Many conditions, including cancer, trauma, and congenital anomalies, can damage the oral mucosa. Multiple cultures of oral mucosal cells have been used for biocompatibility tests and oral biology studies. In recent decades, the clinical translation of tissue-engineered products has progressed significantly in developing tangible therapies and inspiring advancements in medical science. However, the reconstruction of an intraoral mucosa defect remains a significant challenge. Despite the drawbacks of donor-site morbidity and limited tissue supply, the use of autologous oral mucosa remains the gold standard for oral mucosa reconstruction and repair. Tissue engineering offers a promising solution for repairing and reconstructing oral mucosa tissues. Cell- and scaffold-based tissue engineering approaches have been employed to treat various soft tissue defects, suggesting the potential clinical use of tissue-engineered oral mucosa (TEOMs). In this review, we first cover the recent trends in the reconstruction and regeneration of extra-/intra-oral wounds using TEOMs. Next, we describe the current status and challenges of TEOMs. Finally, future strategic approaches and potential technologies to support the advancement of TEOMs for clinical use are discussed.